Experimental investigation of tranverse vibration assisted machining - Ahmed Syed Adnan (2010)
The novel concept of Transverse Vibration Assisted Machining (TVAM) is explored here. Experiments are conducted with and without transverse direction vibration and results compared. The experimental procedure involves orthogonal turning on conventional computer numeric control (CNC) lathe machine using a carbide tool. Aluminium alloy ‘Al-2024’ is used as the workpiece material. In the experimental setup, Branson’s converter/booster assembly and amplitude controller are used to provide the ultrasonic vibration to the cutting tool. The Kistler dynamometer and data acquisition (DAQ) system are used to store the real time cutting force data. The experimental results with respect to tool forces and chips thicknesses obtained from the TVAM setup is compared with that of conventional machining. Also, the surface roughness of machined work piece with different test cases is studied. The experimental results indicate that the tool forces, particularly cutting force reduces by inducing the transverse vibration amplitude during machining. Thrust force also shows the decreasing trend but not for all cases studied. In addition, TVAM also reduces the chip thickness and provides better surface finish when compared to conventional machining.